Konseling Pranikah Untuk Kesiapan Mental Calon Pasangan di Badan Kependudukan dan KB Kota Binjai Pada Masa Pandemi Covid 19 - Muhazir Muhazir; Lilis Saputri; Wadi’ah Noor Hamidah Siregar (INDONESIAN COUNSELING AND PSYCHOLOGY, 2022)
The purpose of this study is to identify the description of premarital counseling for the mental readiness of prospective couples in the Population and Family Planning Board of Binjai City. This study used a qualitative descriptive research method. The subjects of this study were psychologists and prospective partners who took part in the counseling process, and the objects in this study were a psychologist and 4 catin who attended premarital counseling. The results of this study was the implementation model of premarital counseling at the Population and Family Planning Board of Binjai City uses two stages, namely: a) the pre-implementation stage and b) the implementation stage. The counseling model used for the mental readiness of prospective partners uses a group counseling model. At the time of counseling, PUP is introduced, and creates a happy family. The bride and groom come to the Population and Family Planning Board of Binjai City to complete the marriage requirements, gain knowledge about marriage and how to build a happy family so that later they can minimize the problems that come in domestic life.